Papel do IGF-I na infecção por Leishmania amazonensis em macrófagos de indivíduos com deficiência isolada do hormônio do crescimento - Barrios, Mônica Rueda (2014)
Leishmaniasis is a disease that affects humans since ancient times. In the last 20 years an increased number of cases and expansion of the geographic occurrence of leishmaniasis has taken place. In Brazil, the disease is currently found in all states, especially in the North and Northeast regions, with different epidemiological profiles. In vitro studies have shown that the hormone |Insulin-Like Growth Factor| (IGF-I) enhances Leishmania infection in macrophage in vitro and, exacerbates Leishmania infection in vivo in experimental models, treatment with IGF-1. Individuals with a natural mutation of the receptor of growth hormone-releasing hormone (GHRH) and consequent deficiency of growth hormone (GH) and IGF-I have been described in Itabianinha, Sergipe, called Isolated deficiency of growth hormone (DIGH). This mutation affects the growth weight and height, but the immune response of these individuals has not been evaluated. To better understand the role of IGF-1 in susceptibility to Leishmania infection, the purpose of this work was to study the behavior of leishmania infection in vitro in human macrophages from these individuals with IGF-1 deficiency. Leishmania amazonensis infection was compared in monocytes-derived from peripheral blood from two groups of individuals: 1) Individuals affected with homozygous deficiency of GHRH/GH/IGF-I (dwarf phenotype) (n =8), 2) Homozygous controls without this mutation (normal phenotype) (n =7). The number of infected macrophages and the parasitic load/100 macrophages was compared between these groups. These data confirm the data from experimental model that of IGF-I interferes in Leishmania-macrophage interaction, increasing the parasitic load of this infection.